Determining possible sets of leaves for spanning trees of dually chordal graphs - De Caria, Pablo Jesús (2009)
It will be proved that the problem of determining whether a set of vertices of a dually chordal graphs is the set of leaves of a tree compatible with it can be solved in polynomial time by establishing a connection with finding clique trees of chordal graphs with minimum number of leaves.